The Effectiveness of Using Genre Based Approach to Enhance Reading Comprehension in Narrative Text for Young Learners - Nabella, Angelia Cipta Riska; Rini, Setia (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This study focuses on the effectiveness of using Genre Based Approach (GBA) to improve reading comprehension of narrative texts in young learners who have an age range of 11-12 years and aims to determine the level of students' reading ability in the form of narrative text. The classroom Action Research is a research method with pre-test, cycle 1 and cycle II. The researcher finds a positive side from using GBA to enhance reading comprehension in narrative text for young learners. This is evidenced by the significant increase that occurred. Previously, the average score was 63.8, now it has increased to 76.9 in cycle 1. The increase from pre-cycle to cycle I was 13.1 points. Then, in cycle II pupils obtained an average score of 81.9. Furthermore, the increase in students' abilities from cycle I to cycle II increased by 5 points. Thus, students experienced an increase from pre-cycle to cycle II of 18.1 points. Therefore, the results of this study can be used as a reference for educators so they don't hesitate in using GBA as a medium to improve the reading ability of English young learners in the range pf ages 11-12 years. Because besides increasing interest in reading, this research also increase the level of students' critical thinking in analysing readings and finding the main ideas in all elements of narrative text.